2002
DOI: 10.1128/jvi.76.9.4456-4466.2002
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Spring-Loaded Conformational Change of Influenza Virus Hemagglutinin

Abstract: Influenza virus hemagglutinin undergoes a conformational change in which a loop-to-helix "spring-loaded" conformational change forms a coiled coil that positions the fusion peptide for interaction with the target bilayer. Previous work has shown that two proline mutations designed to disrupt this change disrupt fusion but did not determine the basis for the fusion defect. In this work, we made six additional mutants with single proline substitutions in the region that undergoes the spring-loaded conformational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 33 publications
5
61
0
Order By: Relevance
“…Peptides to this region will be useful probes to explore molecular mechanisms of how HSV induces membrane fusion. As with HIV and other viruses, the site at which an inhibitory peptide engages the virus could be a vulnerable target site to develop potent antiviral agents (5,13,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptides to this region will be useful probes to explore molecular mechanisms of how HSV induces membrane fusion. As with HIV and other viruses, the site at which an inhibitory peptide engages the virus could be a vulnerable target site to develop potent antiviral agents (5,13,17).…”
Section: Discussionmentioning
confidence: 99%
“…Some synthetic peptides to coiled coils in viral proteins block membrane fusion mediated by these glycoproteins. For influenza virus HA or HIV gp41, peptides to defined ␣-helix regions interfere with fusion between the virus envelope and a cell membrane (5,13). A synthetic peptide that mimics the predicted coiled coil of B5 specifically inhibits HSV stable binding and entry into B5 polyclonal or transiently transfected porcine cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, this can be done by ligand recognition, protein conformational changes, or posttranslational modifications (PTMs). [1][2][3][4][5] PTMs are especially important in the molecular communication across cellular processes, including signal transduction and the host response to viral infection. [6][7][8][9][10][11][12][13] Viruses must utilize this form of cellular communication for their own nefarious purposes.…”
Section: Introductionmentioning
confidence: 99%
“…White and coworkers have suggested that HA undergoes a spring-loaded conformational change and HA aggregates to form rosette formation (Gruenke et al 2002). The full-length of the cytoplasmic tail of HA has been estimated to be less than 1 nm (Naeve and Williams 1990), whereas the dimensions of GFP are approximately 2.5ϫ2.5ϫ4.5 nm 3 (Yang et al 1996).…”
mentioning
confidence: 99%